Discurso de Roberto H. Todd sobre la historia de la Logia Estrella de Luquillo - Todd, Roberto H. (My University, 1943)
Discurso de Roberto H. Todd sobre la historia de la Logia Estrella de Luquillo.
Keywords: Freemasonry--Puerto Rico.; Masoneria--Puerto Rico.; Palmer, Santiago R.; Torres, Juan Ramón de; Cruz, Arturo de la; Boschetti, Clemente; León, José; Hernández López, Juan; Rivera, Saturnino; Elmendorf, Colton E.; Llauger Díaz, Carlos; Pujals Morey, Juan